Preparation of mesoporous titanosilicate with isolated Ti active centers for cyclohexene oxidation. Issue 112 (28th October 2015) - Gupta, S.; Vinod, C. P.; Jagadeesan, D.
Abstract : We report the preparation of mesoporous titanosilicate catalysts with isolated active Ti centres using CTAB as the structure directing agent and ethylenediamine as the complexing agent (TSC–ED). Abstract : We report the preparation of mesoporous titanosilicate with active Ti centres using CTAB as the structure directing agent and ethylenediamine as the complexing agent (TSC–ED). The final material contained isolated Ti 4+ centres substituting Si 4+ in the mesoporous silica framework. The crucial role played by ethylenediamine in complexing with Ti 4+ during the sol–gel process and preventing the phase segregation of TiO2 was studied systematically. The textural parameters, structural order, morphology, nature and co-ordination of Ti species were analyzed using various techniques such as X-ray diffraction (XRD), UV-vis diffused reflectance spectroscopy (UV-vis DRS), UV resonance Raman spectroscopy, Fourier transformed Infra-red spectroscopy (FT-IR), field emission scanning electron microscopy (FESEM), transition electron microscopy (TEM), and X-ray photoelectron spectroscopy. Finally, the catalysts were tested for catalytic activity in the oxidation of cyclohexene using various oxidants.